BIMBINGAN DAN KONSELING UNTUK ANAK UNDERACHIEVER - Rafika Rahmawati (Paradigma, 2012)
Underachiever is a child with a performance that doesnot comply with the conditions they are supposed to have.Many things can cause a child to be an underachiever. Onereason is the teachers' teaching methods that can not beenjoyed by children as they should. Another cause is thestudent's learning style that can not be accommodated in theclassroom. The condition is often associated with giftedunderachiever. Guidance and counseling to help childrenunderstand the conditions underachiever themselves. In-depthguidance and counseling can also help the child adjust tolearning in the classroom. Parental involvement in thetreatment of children with problems can underachiever positiveeffect on child development.Keywords: underachiever, guidance and counseling.